PERAN BAHAN HUMUS-KALSIUM PADA PUPUK UREA TERHADAP KETERSEDIAAN NITROGEN, PERTUMBUHAN DAN HASIL BAWANG MERAH DI LAHAN PASIR PANTAI - , Sulakhudin, SP.,MP. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Coastal sandy soils, in general, have low fertility because mainly nitrogen losses due to leaching and volatilization. To reduce N losses and increase growth and yield of shallot in coastal sandy soils, Urea fertilizers can be coated or mixed with humic-calcium (humic-Ca). This main study aimed to find out kinds of humic-Ca concentrations which gave the lowest leaching and volatilization N, and the highest growth and yield of shallot in coastal sandy soil. This study consisted of three experiments i.e: (1) laboratory experiment, (2) green house experiment and (3) field experiment at the coastal sandy land of Bugel, Kulon Progo. The study was carried out from March 2008 to April 2009. The results showed that Urea coated with humic-Ca from cow manure and humic-Ca from peat increased the N total and available N higher than Urea mixed humic-Ca from cow manure and humic-Ca from peat in the soil. Compare to all treatments, Urea coated with humic-Ca in all concentration showed nitrate higher than ammonium on incubation length 2, 4 and 6 weeks. Urea coated with humic-Ca 10% was less pronounced in reducing N leaching compared to other treatments. The greatest percentage reduction N volatized on humic-Ca concentration 10 % was 21.21%. Humic-Ca Urea fertilizer can increase the total soil pore. Improved soil pores mainly occur in slow drainage pores showing significant differences with Urea. Increased soil porosity have positive correlation with some soil chemical properties of coastal sandy soil, such as total nitrogen content, NH4 +, NO3 -, organic matter, pH, exchangeable Ca and CEC. The humic-Cacow material provided as a coating of urea has not been able to increase significantly the soil N availability, growth and yield of shallot in the coastal sandy soil than Urea mixed the humic-Ca. The availability of N due to the addition of humic-Cacow material negatively correlated with microbial population ammonification microbial, but positively correlated with soil microbial populations of nitrifying. Urea coated humic-Cacow 50% dose recommendations for optimum growth and yield of shallot in the coastal sandy soil.